(3YbO GdLhGgQ hGdOQ aj CNHGQ GdbQf GdMGOi YTQs - (3eMeO Hf CHj HcQ Hf CMeO GdTdj HGYdhj,J (B1094 (3g` s ((3SGde Hf gGOi Hf CMeO HGUdGeI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTC GdehLhOGJ HHGgQ bOQJg CeG HYO aEf ai GdJGQjg ahGFO LjGOkG hai gPG GdbQf ef YjGf GdCaGVd hCaGVd GdCYjGf s
(3BNQgG (B:s
(3Ke GdUdGI Ydi GdeNJGQ CMeO ef RGdJ HHYKJg GdCghGd hGdeMf hGdBd hGdUMH eGgHJ QjGM GdUHG heG JQfe WjQ hGfKfi ZUf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs